Salivary Biomarker Levels and Periodontal Health Status in Patients with Diabetic and Healthy Lifestyle: A Comparative Study - Farooq Maqsood; Huma Abid; Daud, Nausheen; Naila Noreen; Malik, Faizan Bilal; Tariq Ali Khan (Journal of Gandhara Medical and Dental Science, 2024)
OBJECTIVES To evaluate and compare the periodontal health status and salivary biomarker levels in diabetic patients and non-diabetic individuals, thereby determining the association between these factors. METHODOLOGY A comparative study included 100 participants divided into two groups: 50 diabetic patients and 50 healthy controls. Periodontal parameters such as the gingival index (GI), probing pocket depth (PPD), and clinical attachment level (CAL) were assessed. Salivary biomarkers, including interleukin-6 (IL-6), tumor necrosis factor-alpha (TNF-α), and glucose levels, were measured using enzyme-linked immunosorbent assay (ELISA) techniques. Statistical analysis was conducted using SPSS software. RESULTS Diabetic patients exhibited significantly higher periodontal parameters (GI, PPD, CAL) compared to healthy controls (p < 0.05). Salivary biomarkers, particularly IL-6 and TNF-α, were markedly elevated in the diabetic group (p < 0.01). There was a strong positive correlation between salivary glucose levels and periodontal parameters (p < 0.001). CONCLUSION Diabetic individuals show worse periodontal health and elevated salivary inflammatory biomarkers compared to non-diabetic controls. This suggests a need for closer periodontal monitoring in diabetic patients to mitigate further systemic complications.